MAGNETIC-MOMENTS AND SHAPE COEXISTENCE IN THE LIGHT BR ISOTOPES - Griffiths, A; Ashworth, C; Rikovska, J; Stone, N; White, J; Grant, I; Walker, P; Walters, W (1992)
Low temperature nuclear orientation measurements have been made to study the nuclear magnetic dipole moments of Brg,72m, Brm73,74, Brg75,76, and Brg77 implanted into Fe. The analysis of the data has been performed within the framework of a two, nonzero field, site model to describe the occupation of Br nuclei in the host Fe lattice. The two sites were associated with magnetic hyperfine fields of 81.38(6) and 26(2) T. A spin of 1/2 for the Br73 ground state is deduced and magnetic dipole moments are determined for the remaining nuclides. In addition, conversion electrons were observed for Br72, confirming the multipolarity of the isomeric transition. An interpretation of the ground-state configurations and shapes of these isotopes is given using particle-rotor calculations and it is shown that the Br nuclides can be better described as a hole in the more deformed Kr nuclides rather than a particle beyond the Se cores. © 1992 The American Physical Society.